2017
DOI: 10.1126/scitranslmed.aan1208
|View full text |Cite|
|
Sign up to set email alerts
|

The FcRn inhibitor rozanolixizumab reduces human serum IgG concentration: A randomized phase 1 study

Abstract: Pathogenic immunoglobulin G (IgG) autoantibodies characterize some human autoimmune diseases; their high concentration and long half-life are dependent on recycling by the neonatal Fc receptor (FcRn). Inhibition of FcRn is an attractive new treatment concept for IgG-mediated autoimmune diseases. Rozanolixizumab (UCB7665; CA170_01519.g57 IgG4P) is an anti-human FcRn monoclonal antibody. In cynomolgus monkeys, rozanolixizumab reduced IgG (maximum 75 to 90% by about day 10), was well tolerated, and did not increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
174
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(187 citation statements)
references
References 39 publications
7
174
1
5
Order By: Relevance
“…These results are consistent with previously published data: two humans with β2m-deficiency (and consequently FcRn-deficient) had plasma IgG concentrations of about 11% and 25% of normal, 51 and FcRn-deficient mice had plasma IgG concentrations of about 11.8% of normal. 45 The extent of plasma IgG reduction achieved in these preclinical investigations and in the clinical study 6 are comparable with the reduction (~ 50–60%) observed following a full course of repeated plasmapheresis procedures in humans, which is one of the current standards of care in autoimmune diseases. 52,53 This suggests that FcRn blockade may not only have clinical efficacy in autoimmune disease, but also that it could be more simply and rapidly administered, and may be more convenient and more specific in its mechanism of action than current treatments.…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…These results are consistent with previously published data: two humans with β2m-deficiency (and consequently FcRn-deficient) had plasma IgG concentrations of about 11% and 25% of normal, 51 and FcRn-deficient mice had plasma IgG concentrations of about 11.8% of normal. 45 The extent of plasma IgG reduction achieved in these preclinical investigations and in the clinical study 6 are comparable with the reduction (~ 50–60%) observed following a full course of repeated plasmapheresis procedures in humans, which is one of the current standards of care in autoimmune diseases. 52,53 This suggests that FcRn blockade may not only have clinical efficacy in autoimmune disease, but also that it could be more simply and rapidly administered, and may be more convenient and more specific in its mechanism of action than current treatments.…”
Section: Resultssupporting
confidence: 59%
“…Furthermore, the PK/PD studies reported here in transgenic mice and cynomolgus monkeys showed that rozanolixizumab caused no reduction in plasma albumin concentration outside the normal range; an observation also reported in healthy volunteers. 6 The reductions in albumin observed in the 13-week cynomolgus monkey toxicology study were likely attributed to partial steric hindrance at high concentrations of rozanolixizumab; however, it is important to note that in this study, rozanolixizumab was administered at a concentration 100-fold in excess of the planned human exposure level. In cynomolgus monkeys there was no effect of rozanolixizumab or 1519.g57 Fab’PEG on concentrations of IgM and IgA (which are not recycled by FcRn), these data support the results observed in the clinical healthy volunteer study of rozanolixizumab.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations